Empowering MSMEs in Dlinggo Hamlet through digital marketing as a means of promotion - Andi Widiyanto; Rozaq Sulastiyono; Wahyu Santoso; Surya Abdilah; Muhammad Faisal Rizki; Rachman Perayoga (Universitas Muhammadiyah Magelang, 2022)
Magelang Regency's Dusun Dlinggo, Ngadirejo Village, Tegalrejo District, has become a center for traditional Eid cakes, namely semprong. The month of Ramadan sees the highest demand, with no more orders being taken even in the middle of the month. This community service aims to empower MSMEs by increasing demand for semprong cakes throughout the year through digital marketing and online sales. Through training and assistance in product design, packaging, and management of e-commerce websites and social media, the community is actively involved in the implementation of program. In comparison with before program, the results of measuring partner knowledge of digital marketing increased by 49%.